Prevalence of Psychiatric Comorbidities in Patients with Migraine: A Cross-sectional Study - Hina Bano; Kushagra Varma; Jai Singh; Mohammad Aleem Siddiqui; Abdul Qadir Jilani (Indian Journal of Private Psychiatry)
Aim: To evaluate the prevalence of psychiatric comorbidity in migraine patients. Materials and methods: A total of 60 patients diagnosed with migraine according to the International Classification of Headache Disorders (ICHD-3) were included in the study and were interviewed for depression and mental disorders according to ICD-10 criteria. The migraine disability assessment (MIDAS) questionnaire was used to understand the impact of headaches on patients' lives and the disruption of daily activities. Results: Migraine was more common in women, and while comorbid psychiatric disorders were detected in 42 patients (70%), dissociative disorder was the most common diagnosis (25%). Conclusion: The incidence of psychiatric comorbidities is higher in migraine patients. Dissociative disorders are the most common psychiatric disorders, followed by depression.